What Is Bioethics? - Rodríguez Allen, Ana (2002)
As we will see in this essay, the decision of the Constitutional Chamber on in vitro fertilization was the spark that awakened the public about what is correct and what is not correct in the biomedical field and revealed trends in this discussion. In the case of the national press, only one vision was shown, that of paternalistic medical ethics. And above all, they began to speak of a new field of knowledge called bioethics, but a bioethics with a Costa Rican matrix, which left critical bioethics aside, whose approach shows a new vision that shakes the traditional paradigm of classical medicine.